Model of integrative border diplomacy in managing harmony between Indonesia and Malaysia: case of Temajuk, West Kalimantan, Indonesia - Iva Rachmawati; Machya Astuti Dewi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The discussion about border diplomacy, either by the central government and sub-national actor, is still dominated by the state. The border issues are still considered as part of the security issue that makes the issues belong to the domain of high politics. In turn, this point of view makes the state the only actor in the management of the borderline area and border diplomacy. This paper is going to propose an integrative type of border diplomacy as a model to study borderline diplomacy. This model introduces the roles of the three actors, namely, central government as the main actor, sub-national actors, and non state actors as supporting actors. Based on an empirical study conducted through field research in Temajuk, Sambas, West Kalimantan, Indonesia, this paper argues that the collaboration of the three actors plays an important role in resolving the conflict in the borderland of Indonesia-Malaysia. National government of the Republic of Indonesia, local government of Sambas and Temajuk as sub-national actors, and supporting actors: community, academicians, and local mass media synergized in administering borderline diplomacy. In this interaction, sub-national actors played the most intensive role in seeking the resolution. In turn, this symbiosis supports the harmony between Indonesia-Malaysia in border area.